4f(x-6)-2=0

Simple and best practice solution for 4f(x-6)-2=0 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4f(x-6)-2=0 equation:


Simplifying
4f(x + -6) + -2 = 0

Reorder the terms:
4f(-6 + x) + -2 = 0
(-6 * 4f + x * 4f) + -2 = 0
(-24f + 4fx) + -2 = 0

Reorder the terms:
-2 + -24f + 4fx = 0

Solving
-2 + -24f + 4fx = 0

Solving for variable 'f'.

Move all terms containing f to the left, all other terms to the right.

Add '2' to each side of the equation.
-2 + -24f + 2 + 4fx = 0 + 2

Reorder the terms:
-2 + 2 + -24f + 4fx = 0 + 2

Combine like terms: -2 + 2 = 0
0 + -24f + 4fx = 0 + 2
-24f + 4fx = 0 + 2

Combine like terms: 0 + 2 = 2
-24f + 4fx = 2

Reorder the terms:
-2 + -24f + 4fx = 2 + -2

Combine like terms: 2 + -2 = 0
-2 + -24f + 4fx = 0

Factor out the Greatest Common Factor (GCF), '2'.
2(-1 + -12f + 2fx) = 0

Ignore the factor 2.

Subproblem 1

Set the factor '(-1 + -12f + 2fx)' equal to zero and attempt to solve: Simplifying -1 + -12f + 2fx = 0 Solving -1 + -12f + 2fx = 0 Move all terms containing f to the left, all other terms to the right. Add '1' to each side of the equation. -1 + -12f + 1 + 2fx = 0 + 1 Reorder the terms: -1 + 1 + -12f + 2fx = 0 + 1 Combine like terms: -1 + 1 = 0 0 + -12f + 2fx = 0 + 1 -12f + 2fx = 0 + 1 Combine like terms: 0 + 1 = 1 -12f + 2fx = 1 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.

See similar equations:

| 5y+9=12y+9 | | 24+m= | | -6-8=6x+9-5x | | .3(b+6)=.75b+8 | | 7x-12-4x=7x-9 | | 15-z=27 | | 6p^2+5p+1=0 | | x^2+23x+13= | | 345789943v=5 | | 4y-7=12y+2 | | x+(8)3=66 | | 6x-2(x-2)=4(x+1)+2 | | 6p^2-15p+1=0 | | 3x+50+4x+32=180 | | 12(2+m)= | | 5(3x-1)-2(x+3)=8(x+1) | | 15x-9=45x+15 | | (x+2)(x)(6)=420 | | 4f(x-6)-2=x | | 4f(x-6)-2=y | | 3x(x-7)=6(x^2)-22x | | (u+3)(u)=65 | | 27=3x-3(6-2x) | | 9x-(x-3)=7(x+1)+8 | | 9=14 | | -54(x-94)=x+37 | | 6x^2+12x-420=0 | | 2(5c-1)-12=8c+2 | | z-14=-22 | | 3x+2-4=-2 | | 3y+2(y-2)=7y-4(y-10) | | 9x-3(6+x)+32= |

Equations solver categories